Facile generation and regulation of oxygen vacancies in BiOCl catalysts for effectively photocatalytic degradation of Rhodamine B - Fei Pei; Xin'’e Yan; Jiajie Dong; Youwen Xu; Songyuan Yao; Wei Zhao (Results in Chemistry)
Introducing oxygen vacancies (OVs) in BiOCl catalyst has been regarded as an effective strategy in broadening the narrow range of light response and enhance separation efficiency of photo-induced carriers. However, the commonly-used methods for OVs generation are mostly realized under relatively harsh conditions. Herein, spherical BiOCl microparticles with abundant OVs assembled from nanosheet were synthesized via a mild one-step hydrothermal method. In addition, the concentration of OVs can be simply regulated via adjusting the mount of additives. The as-prepared BiOCl-3 samples presented the most favorable photocatalytic properties in decomposing Rhodamine B (RhB) under visible light via the improved separation efficiency of photo-induced carriers by sufficient OVs and more active sites due to large specific surface area for physical adsorption and photocatalytic decomposition. The degradation ratio of RhB reaches approximately 100 % within 48 min under BiOCl-3 catalysis, and the RhB degradation ratio still maintained a ratio of 90 % after four consecutive cycles. This work provides a beneficial reference for facile generation and regulation of OVs in photocatalysts with highly photocatalytic performance.